Fatigue life estimations of alclad AA2024-T3 friction stir clinch joints. (February 2018) - Lin, P.-C.; Lo, S.-M.; Wu, S.-P.
Graphical abstract: Highlights: FSC process can join surface-treated sheet metals with good strength & short time. Fatigue behaviors of FSC joints in TS & CT specimens were investigated. Critical fatigue cracks and failure modes were identified. Fatigue lives were well estimated by interfacial & kinked crack fatigue models. Fatigue data of FSC joints were well correlated by effective global & local SIFs. Abstract: Joining alclad AA2024-T3 sheets is difficult for conventional welding processes due to ductile surface cladding layers. Friction stir clinching (FSC) was therefore proposed to overcome this problem. Here, two types of specimens, tensile-shear and cross-tension, were made to investigate general fatigue behavior of FSC joints. Critical fatigue cracks and failure modes were identified by photos and micrographs. Interfacial and kinked crack fatigue models consist of local and global stress intensity factors (SIFs) and a Paris law approach were taken for fatigue life estimations. The fatigue life estimations well agreed with the experimental fatigue data. The fatigue data of FSC joints in above specimens were well correlated by effective SIF ranges.